BIM for Facility Management: Challenges and Research Gaps - S. Neda Naghshbandi (Civil Engineering Journal, 2016)
This writing presents research gaps in the area of Building Information Modelling (BIM) in Facility Management (FM) industry, and identifies practical challenges that facility management professionals are facing in utilizing BIM. Although this issue, BIM for Facility Management, has gained attention both in literature and practice, and it is highly demanded in FM industry, still it is far away from effective implementation. It is not clear for facility manager whether BIM is helpful to accelerate the process or it is a cost effective solution, and what skills are required for them. The key for effective BIM implementation in FM industry is to enhance collaboration among different parties in project lifecycle. However, still there is a doubt about the importance of FM in Construction industry. In other words, construction does not understand FM. Furthermore, there are issues over interoperability and data exchange. Thus, to assist BIM implementation, it is required to prove the correctness of benefits, uses, and challenges identified in the literature. This paper uses an intensive literature review and highlights the potential research issues in terms of BIM for FM to assist effective implementation of BIM in facility management phase of projects.